Finite-population 'Mass-Action' and evolutionary stability - Axel Bernergard; Karl Wärneryd (Center for Economic Studies and ifo Institute (CESifo), 2011)
Nash proposed an interpretation of mixed strategies as the average pure-strategy play of a population of players randomly matched to play a normal-form game. If populations are finite, some equilibria of the underlying game have no such corresponding 'mass-action' equilibrium. We show that for mixed strategy equilibria of 2 2 games, the requirement of such a correspondence is equivalent to neutral evolutionary stability.
Keywords: C72; C73; 330; mass action; finite population games; evolutionary stability; Nichtkooperatives Spiel; Evolutionäre Spieltheorie; Theorie